Drone air quality measurements during flight MesSBAR_2021-09-23_flight7 - Andreas Schlerf; Lutz Bretschneider; Malte Schuchard; Sebastian Düsing; Ralf Käthner; Birgit Wehner; Tobias Schuldt; Christian Wesolek; Ralf Tillmann; Anne Caroline Lange; Hassnae Erraji; Thomas Krüger; et al. (PANGAEA, 2024)
In the project MesSBAR (Automated airborne measurement of pollution in the near-earth atmosphere in urban areas), unmanned aerial systems and specially adapted air quality measurement technology were developed to carry out measurements upwind and downwind of pollution sources in urban areas, industrial plants and traffic routes. To validate and optimise the measurement technology and flight systems, two short measurement campaigns were carried out in 2021 near Wesseling next to the motorway A555 (North Rhine-Westphalia - Germany). There, the Federal Highway Research Institute (BASt) operates two measurement containers next to the motorway, which were used for the validation. Various flight profiles were tested. It was found that only for vertical ascents at a constant speed, useful results of the air quality measurements could be determined. The measurement data from these flights are published in this data publication.
In: Schlerf, A et al. (2024): Validation and optimization of the drone air quality measurement system MesSBAR [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.971503